The Effect of Tax Incentives on Local Private Investments and Entrepreneurship: Evidence from the Tax Cuts and Jobs Act of 2017 - Xu, Jiajie (Journal of Financial and Quantitative Analysis, 2026)
An abstract is not available for this content so a preview has been provided. Please use the Get access link above for information on how to access this content.